Variabilidad poblacional en el género Kentropyx (Squamata: teiidae) del Norte argentino - Tedesco, María Esther (1994)
Variability of population of Kentropyx from northern Argentina was studied using characters of lepidosis and coloration. A subspecific taxonomic level, Kentropyx viridistriga lagartija is proposed for Kentropyx lagartija, considering this subspecies a western form of the eastern one Kentropyx viridistriga viridistriga.